Linear damage localization in CFRP laminates using one single fiber-optic Bragg grating acoustic emission sensor. (15th April 2020) - Yu, Fengming; Okabe, Yoji
Abstract: Highly sensitive ultrasonic fiber-optic Bragg gratings (FBGs) have been used as acoustic emission (AE) sensors in the non-destructive inspection (NDI) for analyzing damage progression during the material tests of carbon fiber reinforced plastic (CFRP) laminates. Localization of the damage-induced AE source is one of the desirable functions for enhancing the efficiency of the AE-based NDI method. Hence, we attempted to establish a linear source localization method in a coupon-shaped CFRP test specimen with a highly sensitive FBG sensor. In particular, to protect the FBG-AE detection from influence caused by the static strain in a test specimen, the FBG sensor was installed by a remote adhesive configuration, i.e., one point of optical fiber was glued on the specimen, and the FBG sensor in the optical fiber was located away from the adhesive point. In the particular bonding way, the FBG sensor detected AE wave through an optical-fiber-based ultrasonic waveguide. In the first half of the paper, an ultrasonic experiment was conducted to show this installation technique can stably and accurately detect the behavior of Lamb wave modes in AE signals. With the help of the sensing characteristics, we clarified that a time difference between the arrival of S0 and A0 modes in a one AE signal had a linear relation to the distance between the AE source and the adhesion point when the length of optical fiber-based waveguide was fixed. Based on the examination, the linear AE source localization method was established using only one single FBG sensor. After confirming the ability of the proposed approach through a simulated AE experiment in a cross-ply CFRP laminate, we used the strategy to localize the actual damage-induced AE sources during a three-point bending test of the laminate.